Therapeutic reference range for olanzapine in schizophrenia: systematic review on blood concentrations, clinical effects, and dopamine receptor occupancy - Wesner, Katja; Hiemke, Christoph; Bergemann, Niels; Egberts, Karin M.; Fekete, Stefanie; Gerlach, Manfred; Havemann-Reinecke, Ursula; Lense, Xenija M.; Riemer, Thomas G.; Schoretsanitis, Georgios; Uhr, Manfred; Zernig, Gerald; et al. (The journal of clinical psychiatry, 2023)
Objective: Aiming at revising the therapeutic reference range for olanzapine, the present study highlights the association between blood olanzapine levels, clinical effects, and dopamine D2-receptor occupancy for oral and long-acting injectable (LAI) formulations. Data Sources: Databases were systematically searched for randomized controlled trials (RCTs) and uncontrolled trials concerning blood olanzapine levels in relation to clinical outcomes or D2-receptor occupancy using MEDLINE (PubMed), Web of Science, PsycINFO, and Cochrane Library (March 2021, updated in December 2021). We excluded articles not written in English or German and non-human data. Search terms included olanzapine, blood level, drug monitoring, PET, and SPECT. Study Selection: The process of study selection followed a previously published protocol and PRISMA guidelines. A total of 2,824 articles were identified through database search and 1 article via reference list check. Thirty-four studies were suitable for qualitative synthesis, and 13 studies were included in the quantitative analysis. Data Extraction: Reviewers performed data extraction and quality assessment of the included studies independently following the review protocol. Results: Evidence for a relationship between blood olanzapine level and efficacy/side effects (constipation) is considered low (Level C). In total, 3 studies of moderate quality consistently showed therapeutic thresholds of around 20 ng/mL for olanzapine 12 hours post-dose. This threshold is in line with findings from positron emission tomography (PET) studies that suggest optimal drug efficacy (65%-80% D2-receptor occupancy) between 17 and 44 ng/mL. Conclusions: We suggest a therapeutic reference range of 20-40 ng/mL for olanzapine oral and LAI formulations. In this range, optimal treatment response is expected in patients with schizophrenia and schizophrenia spectrum disorders. Side effects, especially weight gain, may already occur at therapeutic levels. However, higher plasma concentrations are in general well tolerated and should not necessarily require a dose reduction in case of good response and tolerance.